Mesin Pengayun Penapis Tepung Menggunakan Motor AC - Siti Paridah Juhari; Juliyanna Aliman; Abdul Hadi Puad (Jurnal INOVATOR, 2023)
The project study is based on observation and applies to the present manual method of filtering flour with a standard filter. The research study aims to create a flour sifting machine that is appropriate for small business owners. The scope of the study that has been set is to focus on small and medium industrial cake makers. A medium-sized machine is designed to facilitate lifting and moving for users. It addresses a number of issues with the use of existing methods, such as the use of a lot of manpower in the process of sifting flour, the length of time required if the old method is used, and the inability to sift huge amounts of flour. The material used must have special characteristics, i.e. it does not rust and does not affect food. Research indicates that stainless steel is the most appropriate. While for the component formation process, methodological studies are used to plan the project production process by using flow charts as a guide for project planning, production and testing. As a result, the average rate of time saving of sifting flour using this machine compared to the manual method is 26.67%. Based on the results, analysis and discussions that have been carried out, it can be concluded that the "Flour Filter Oscillating Machine Using AC Motor" has achieved its objective. Furthermore, it has been demonstrated that this equipment can save time when compared to manual labor.